The ifo Education Survey 2014-2021 - Vera Freundl; Elisabeth Grewenig; Franziska Kugler; Philipp Lergetporer; Ruth Schueler; Katharina Wedel; Katharina Werner; Olivia Wirth; Ludger Woessmann (Ludwig-Maximilians-Universität München und Humboldt-Universität zu Berlin, Collaborative Research Center Transregio 190 - Rationality and Competition, 2023)
The ifo Education Survey is a representative opinion survey of the German voting-age population on education topics that has been conducted annually since 2014. It covers public preferences on a wide range of education policy issues ranging from early childhood education, schools, and apprenticeships to university education and life-long learning. The dataset comprises several survey experiments that facilitate investigating the causal effects of information provision, framing, and question design on answering behavior. This paper gives an overview of the survey content and methodology, describes the data, and explains how researchers can access the dataset of over 4000 participants per wave.
Keywords: I28; D72; H52; 330; education; policy; survey; experiment; public opinion; political economy; Germany